2005
DOI: 10.1017/s1049023x00002296
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Stress among Japanese Emergency Medical Technicians: Hyogo Prefecture

Abstract: Introduction:As prehospital care became emphasized in emergency medical services in Japan, qualification as a “paramedic” was established in 1991 as a requirement for national qualification as a emergency medical technician (EMT).With recent increases in emergency transportation, the responsibilities of paramedics have become more complex and demand a higher level of competency; however, no method of evaluating occupational stress among Japanese EMTs currently exists.Methods:A questionnaire survey of the worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 12 publications
4
49
1
4
Order By: Relevance
“…In addition, this concurs with other studies, which have found that ambulance personnel report higher levels of musculoskeletal strain than employees in other health services,(4) and that ambulance personnel self-report more musculoskeletal and physical health problems than the general population. (1819)…”
Section: Resultsmentioning
confidence: 99%
“…In addition, this concurs with other studies, which have found that ambulance personnel report higher levels of musculoskeletal strain than employees in other health services,(4) and that ambulance personnel self-report more musculoskeletal and physical health problems than the general population. (1819)…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that some healthcare workers are at high risk of musculoskeletal disorders, particularly low back pain (2). The Nurses and paramedic staffs, especially ambulance paramedics who work in prehospital emergency medical system (PEMS), are at high risk of back pain due to the nature of their services, encountering stressful conditions, strenuous physical activities such as handling patients, bad work environment, and long-time standing (3-5). Additionally, ambulance paramedics are vulnerable to physical disorders that cause back pain not only because they involve in caring, handling injured patients, and transporting patients with acute or chronic disorders, but also should work under abnormal circumstance such as the scene of accidents, natural disasters, and the confined space in the ambulance.…”
mentioning
confidence: 99%
“…Accordingly, it is not surprising that studies have also shown that occupational injury rates are higher among female ambulance workers than males. 20,31 Regardless, large differences in the strength capacities between paramedics means that some may need to strain at near maximum effort to achieve the same outcome as another paramedic who is well within their comfortable range of effort. 2,19,24 Importantly, the strength requirements of a modern paramedic have not been examined and so care should be used before over-interpreting these data.…”
Section: Discussionmentioning
confidence: 99%